Етнографічно-фольклористичний набуток Зенона Кузелі - Погребенник, В. (Народна творчість та етнографія, 2006)
Professor Zenon Kuzelya (1882—1952) was a great scientific and public leader. He belonged to those scholars of the 20th century who cherished free Ukrainian science and represented it for the world. A talented ethnologist and folklorist, a lexicographer and bibliographer, he is not well known in Ukraine. The research on the scholar's personality and his scientific work based on the rare publications and archives sources aims to show Z. Kuzelya's life and creative achievements, to invite the reader into the scholar's workshop, to line out the place and meaning of his works in the Ukrainian science.